Interleukin 24 promotes cell death in renal epithelial cells and is associated with acute renal injury. Issue 11 (16th July 2022) - Schütte‐Nütgen, Katharina; Edeling, Maria; Kentrup, Dominik; Heitplatz, Barbara; Van Marck, Veerle; Zarbock, Alexander; Meersch‐Dini, Melanie; Pavenstädt, Hermann; Reuter, Stefan
Abstract: Ischemia–reperfusion injury is a major cause of acute kidney injury. Many cytokines are involved in the pathogenesis of renal ischemia–reperfusion injury. IL24 is a member of the IL10 family and has gained importance because of its apoptosis‐inducing effects in tumor disease besides its immunoregulative function. Littles is known about the role of IL24 in kidney disease. Using a mouse model, we found that IL24 is upregulated in the kidney after renal ischemia–reperfusion injury and that tubular epithelial cells and infiltrating inflammatory cells are the source of IL24. Mice lacking IL24 are protected from renal injury and inflammation. Cell culture studies showed that IL24 induces apoptosis in renal tubular epithelial cells, which is accompanied by an increased endoplasmatic reticulum stress response. Moreover, IL24 induces robust expression of endogenous IL24 in tubular cells, fostering ER‐stress and apoptosis. In kidney transplant recipients with delayed graft function and patients at high risk to develop acute kidney injury after cardiac surgery IL24 is upregulated in the kidney and serum. Taken together, IL24 can serve as a biomarker, plays an important mechanistic role involving both extracellular and intracellular targets, and is a promising therapeutic target in patients at risk of or with ischemia‐induced acute kidney injury. Abstract : In vitro and in vivo study shows that, during kidney ischemia / reperfusion injury, interleukin 24 induces apoptosis and endoplasmic reticulum stress in renal tubular epithelial cells, leading to acute kidney injury.